Range Sensor Overview and Blind-Zone Reduction of Autonomous Vehicle Shuttles. Issue 1 (May 2021) - Gu, Junyi; Chhetri, Tek Raj
Abstract: In recent years, with the advancement in sensor technologies, computing technologies and artificial intelligence, the long-sought autonomous vehicles (AVs) have become a reality. Many AVs today are already driving on the roads. Still, we have not reached full autonomy. Sensors which allow AVs to perceive the surroundings are keys to the success of AVs to reach full autonomy. However, this requires an understanding of sensor configurations, performance and sensor placements. In this paper, we present our experience on sensors obtained from AV shuttle ise Auto. An AV shuttle ise Auto designed and developed in Tallinn University of Technology is used as an experimental platform for sensor configuration and set-up.